2020
DOI: 10.1093/ajh/hpaa169
|View full text |Cite
|
Sign up to set email alerts
|

Serum ACE2, Angiotensin II, and Aldosterone Levels Are Unchanged in Patients With COVID-19

Abstract: Background The role of the renin-angiotensin-aldosterone system in COVID-19 is controversially discussed. SARS-CoV-2 enters host cells by binding to angiotensin-converting enzyme 2 and activity of the renin-angiotensin-aldosterone system may affect susceptibility to SARS-CoV-2 infection and outcome of patients with COVID-19. Methods In this prospective single-center study, we determined the serum levels of ACE-2, angiotensin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
83
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(103 citation statements)
references
References 16 publications
8
83
4
1
Order By: Relevance
“…Baseline ACE2 levels did not show statistically significant differences between COVID-19 positive and negative patients, which is in line with the results of a recent study with a much smaller sample size. 39 The associations between high plasma levels of ACE2 and worse WHOmax category during 28 days were more pronounced in COVID-19 positive patients compared with COVID-19 negative patients but the difference was not significant in the two-way ANOVA analysis. It is therefore not possible with this dataset to conclude whether differences in ACE2 levels are specifically associated with disease outcome in patients with COVID-19 positive disease only.…”
Section: Discussionmentioning
confidence: 81%
“…Baseline ACE2 levels did not show statistically significant differences between COVID-19 positive and negative patients, which is in line with the results of a recent study with a much smaller sample size. 39 The associations between high plasma levels of ACE2 and worse WHOmax category during 28 days were more pronounced in COVID-19 positive patients compared with COVID-19 negative patients but the difference was not significant in the two-way ANOVA analysis. It is therefore not possible with this dataset to conclude whether differences in ACE2 levels are specifically associated with disease outcome in patients with COVID-19 positive disease only.…”
Section: Discussionmentioning
confidence: 81%
“…However, the role of sACE2 levels as a potential risk marker of severe COVID-19 is controversial (Rieder et al, 2020 ; Rojas et al, 2020 ). sACE2 levels are higher in males, increase with age and are associated with BMI and the metabolic syndrome (Kornilov et al, 2020 ; Sama et al, 2020 ; Sward et al, 2020 ), which are both described as risk factors for severe COVID-19 (Grasselli et al, 2020 ; Suleyman et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…AngII concentrations could be markedly reduced, whereas protective Ang1–7 profoundly increased by injecting human recombinant soluble ACE2 in a recent study, leading to a reduction of inflammatory cytokines and improved clinical condition [ 173 ]. In contrast, two studies reported no changes in plasma angiotensin II levels in SARS-CoV-2 infected patients [ 176 , 177 ]. However, patients in both studies did not suffer severe COVID-19 compared to the Wuhan cohort, where all patients suffered pneumonia and/or ARDS [ 172 ].…”
Section: Summary Of Study Findings: Tras and Its Tole In Human Tismentioning
confidence: 99%